2019
DOI: 10.1007/s40519-019-00688-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the genetics and epigenetics of bulimia nervosa/bulimia spectrum disorder and comorbid borderline personality disorder (BN/BSD-BPD): a systematic review

Abstract: PurposeTo evaluate and understand the genetic and epigenetic basis of bulimia nervosa/bulimia spectrum disorder and comorbid borderline personality disorder (BN/BSD-BPD).MethodsThe present systematic review was conducted in accordance to PRISMA guidelines. Advanced systematic searches of Medline, EMBASE, PsychINFO, Web of Science, Scopus, CINHAL plus, and the Cochrane Library were conducted using the search terms ‘bulimia nervosa’, ‘bulimia spectrum disorder’, ‘borderline personality disorder’, ‘genes’, and ‘g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…In fact, it is interesting For more information, visit: http://www.prisma-statement.org/ to note how, in the two studies that examined in greater depth the comorbidity between FED and personality clusters (Udo & Grilo, 2019;Valente et al, 2017), a statistically significant association emerges between BPD and FED, in particular with AN and BN. This result, in agreement with other findings in the literature (Martinussen et al, 2016;McDonald, 2019;Shah & Zanarini, 2018;Newton, 2019;Khosravi, 2020), could be due to the multiple facets of BPD and its traits, which covers various clinical areas (APA, 2014;Gestri, Pazzagli, & Ugolini, 2016). According to what was reported in a recent article by Newton (2019) (Newton, 2019) in fact, a comorbidity between BPD and FED emerges, in particular with: 20% of outpatient patients with bingeing / elimination conducts type AN and 50% of patients with BN (Newton, 2019;Maranon, Echeburia, & Grijalvo, 2007).…”
Section: Summary Of Findingssupporting
confidence: 92%
“…In fact, it is interesting For more information, visit: http://www.prisma-statement.org/ to note how, in the two studies that examined in greater depth the comorbidity between FED and personality clusters (Udo & Grilo, 2019;Valente et al, 2017), a statistically significant association emerges between BPD and FED, in particular with AN and BN. This result, in agreement with other findings in the literature (Martinussen et al, 2016;McDonald, 2019;Shah & Zanarini, 2018;Newton, 2019;Khosravi, 2020), could be due to the multiple facets of BPD and its traits, which covers various clinical areas (APA, 2014;Gestri, Pazzagli, & Ugolini, 2016). According to what was reported in a recent article by Newton (2019) (Newton, 2019) in fact, a comorbidity between BPD and FED emerges, in particular with: 20% of outpatient patients with bingeing / elimination conducts type AN and 50% of patients with BN (Newton, 2019;Maranon, Echeburia, & Grijalvo, 2007).…”
Section: Summary Of Findingssupporting
confidence: 92%
“…Such effects are reported to occur even when the individual has not had direct contact with the trauma itself or the traumatized relative [85][86][87][88][89]. DNA methylation, which is a measure of epigenetic change and which ostensibly mediates such effects, has been associated with a number of changes in mental illness phenotypic manifestations, including brain structure and function, that are relevant to EDs, PTSD and other trauma-related disorders [76][77][78][90][91][92][93][94][95][96][97][98][99]. Significantly, DNA methylation alterations in AN have been shown to be indicative of chronicity and illness severity but can be 'reset' and normalize with treatment and remission of illness [100].…”
Section: Generational Embodiment (Genetics) / Historical Trauma (Epig...mentioning
confidence: 99%
“…A). 19 Altered NR3C1 methylation is associated with early exposure to stress and has the potential to lead to psychological conditions, including major depressive disorder, 20 bipolar disorder, 21 SCZ, 22 post-traumatic stress disorder, 23 bulimia nervosa, 24 and borderline personality disorder. 25 Studies reported that environmental factors causing alterations in epigenetic mechanisms could be related to the HPA axis and suicide.…”
Section: Introductionmentioning
confidence: 99%